Palladium-tin nano-catalyst with mixed phase structure as well as preparation and application thereof
By displacing the tin nanosheets with sodium chloropalladium in DMSO, a mixed-phase structure palladium-tin nanocatalyst was prepared, which solved the problem of low efficiency of palladium-based nanocatalysts in ethanol oxidation reaction, achieving efficient catalytic effect and reducing the production costs.
Patent Information
- Application Number
- CN202411262944.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-17
AI Technical Summary
The existing palladium-based nanocatalysts have low ethanol oxidation reaction efficiency in direct ethanol fuel cell anode, and poor controllability of the multiphase structure, which hinders the overall output power of the fuel cell.
By performing a replacement reaction of tin nanosheets and sodium chloropalladium in DMSO and combining temperature control, a mixed-phase structure palladium tin nanocatalyst with face-centered cubic and ordered intermetallic structure was prepared.
The method has simple steps, short cycle and high yield, which reduces energy consumption and production costs, significantly improves the efficiency of electrocatalytic reaction of ethanol oxidation, and is suitable for large-scale industrial production and application.
Smart Images

Figure CN119153711A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano catalysts, and in particular relates to a mixed phase structure palladium tin nano catalyst and the preparation and application thereof. Background Art
[0002] Palladium-based nanocatalysts are one of the commonly used catalysts in fuel cell catalytic reactions. Among different types of fuel cells, direct ethanol fuel cells have attracted widespread attention due to their easy access and transportation of raw materials and environmental friendliness. Among them, the electrocatalytic oxidation of ethanol is one of the most important catalytic reactions in the anode of direct ethanol fuel cells. However, compared with the efficiency of the hydrogen oxidation reaction at the cathode, the efficiency of the ethanol oxidation reaction at the anode is far lower, which seriously hinders the overall output power of the fuel cell.
[0003] Palladium-based catalysts have shown their unique advantages in the electrocatalytic reaction of ethanol due to their good oxygen affinity, but their efficiency is still far from practical application. Recent studies have shown that the construction of a multiphase structure of palladium-based catalysts can regulate the reaction path of ethanol oxidation and increase the selectivity of the C1 reaction path with 12 electron transfer processes, thereby promoting the efficiency of the electrocatalytic reaction of ethanol.
[0004] In summary, constructing a multiphase palladium-based catalyst structure can effectively promote its catalytic efficiency in the ethanol electrocatalytic reaction, but the current experimental method for obtaining this multiphase structure is relatively complicated, and the controllability of the multiphase structure is poor. Summary of the invention
[0005] The purpose of the present invention is to provide a mixed-phase structured palladium-tin nanocatalyst and its preparation and application, and to obtain a mixed-phase structured palladium-tin nanocatalyst through a replacement reaction to improve the catalytic efficiency.
[0006] The present invention adopts the following technical scheme: a method for preparing a mixed phase structure palladium tin nanocatalyst, comprising:
[0007] Dispersing tin nanosheets and sodium chloropalladate in DMSO, and ultrasonicating to obtain a uniform mixed solution; wherein the molar ratio of the tin nanosheets and sodium chloropalladate in the uniform mixed solution is (1-4):1;
[0008] The mixed solution is stirred uniformly at 140-190° C. until the reaction is completed to obtain a mixed phase structure palladium tin nanocatalyst; the mixed phase structure palladium tin nanocatalyst is a mixed phase structure of face-centered cubic and ordered intermetallic structure.
[0009] Preferably, the preparation method of tin nanosheets is:
[0010] Tin acetylacetonate, polyvinyl pyrrolidone and ammonium bromide were weighed and dispersed in a mixed solution of ethylene glycol and dimethylacetamide, and reacted at 180° C. After the reaction was completed, the solution was cooled and centrifuged to obtain tin nanosheets.
[0011] Preferably, it includes:
[0012] Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheet solution in 2 mL of DMSO and stir by ultrasonic until completely dissolved to obtain a uniform mixed solution;
[0013] The uniformly mixed solution was placed at 180°C until the reaction was completed;
[0014] The solution after the reaction was centrifuged and washed to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.38 .
[0015] Preferably, the preparation method of tin nanosheets is:
[0016] Disperse 1 mL of tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone, and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide;
[0017] The dispersed mixed solution is placed at 180° C. for reaction, and a tin nanosheet solution is obtained after the reaction is completed.
[0018] Preferably, obtaining the tin nanosheet solution further comprises:
[0019] After centrifugation and washing of the tin nanosheet solution, tin nanosheets are obtained;
[0020] The tin nanosheets are dispersed in an ethanol solution for storage.
[0021] Another technical solution of the present invention: a mixed phase structure palladium tin nanocatalyst, wherein the mixed phase structure palladium tin nanocatalyst is a mixed phase structure of face-centered cubic and ordered intermetallic structure.
[0022] Another technical solution of the present invention: application of mixed-phase structured palladium-tin nanocatalysts, wherein the mixed-phase structured palladium-tin nanocatalysts are used in the electrocatalytic reaction of ethanol oxidation.
[0023] The beneficial effects of the present invention are as follows: the present invention uses tin nanosheets and sodium chloropalladate to carry out a replacement reaction, and combines the reaction temperature to control the reaction rate, so as to obtain a palladium-tin nanocatalyst with a mixed phase structure. The method has simple steps, a short cycle, a high yield, good repeatability, and reduces energy consumption and production costs, and is very suitable for industrial large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a bright field transmission electron microscope image of the product in Example 1 of the present invention;
[0025] Figure 2 This is a dark field transmission electron microscope image of the product in Example 1 of the present invention;
[0026] Figure 3 This is a high-resolution transmission electron micrograph of the product in Example 1 of the present invention;
[0027] Figure 4 A high-resolution transmission electron micrograph of another region of the product in Example 1 of the present invention;
[0028] Figure 5 is the X-ray diffraction pattern of the product in Example 1 of the present invention;
[0029] Figure 6 This is a statistical diagram of the size of the product in Example 1 of the present invention;
[0030] Figure 7 This is a bright field transmission electron microscope image of the product in Example 2 of the present invention;
[0031] Figure 8 This is a bright field transmission electron microscope image of the product in Example 3 of the present invention;
[0032] Fig. 9 This is a bright field transmission electron microscope image of the product in Example 4 of the present invention;
[0033] Fig.10 This is a bright field transmission electron microscope image of the product in Example 5 of the present invention;
[0034] Fig.11 This is a bright field transmission electron microscope image of the product in Example 6 of the present invention;
[0035] Fig.12 The cyclic voltammetry curve of the palladium-tin nanocatalyst with an intermetallic phase structure in the application example of the present invention;
[0036] Fig.13 The ethanol oxidation curves of the intermetallic phase structure palladium tin nanocatalyst and commercial palladium carbon in the application examples of the present invention are normalized by mass;
[0037] Fig.14 It is an area-normalized ethanol oxidation curve diagram of the intermetallic phase structure palladium-tin nanocatalyst and commercial palladium-carbon in the application example of the present invention;
[0038] Fig.15 The mass activity bar graph of the intermetallic phase structure palladium tin nanocatalyst and commercial palladium carbon in the application example of the present invention (ethanol oxidation);
[0039] Fig.16This is a bar graph showing the area activity of the intermetallic phase structure palladium-tin nanocatalyst and commercial palladium-carbon in the application example of the present invention (ethanol oxidation). DETAILED DESCRIPTION
[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0041] The microscopic nanostructure of the catalyst is closely related to its catalytic performance. Therefore, it is very important to regulate the microstructure of the palladium-based catalyst to obtain higher ethanol oxidation catalytic efficiency to meet its practical application.
[0042] The invention discloses a preparation method of a mixed-phase structure palladium-tin nanocatalyst, comprising: dispersing tin nanosheets and sodium chloropalladate in DMSO, and ultrasonically obtaining a uniform mixed solution; wherein the molar ratio of the tin nanosheets and the sodium chloropalladate in the uniform mixed solution is (1-4):1; stirring the uniform mixed solution at 140-190°C until the reaction is completed to obtain a mixed-phase structure palladium-tin nanocatalyst; the mixed-phase structure palladium-tin nanocatalyst is a mixed-phase structure of a face-centered cubic structure and an ordered intermetallic structure.
[0043] The present invention uses tin nanosheets and sodium chloropalladate to carry out a replacement reaction, and combines the reaction temperature to control the reaction rate, so as to obtain a palladium-tin nanocatalyst with a mixed phase structure. The method has simple steps, short cycle, high yield, good repeatability, reduced energy consumption and production cost, and is very suitable for industrial large-scale production and application.
[0044] In one embodiment, the preparation method of tin nanosheets is as follows: tin acetylacetonate, polyvinyl pyrrolidone and ammonium bromide are weighed and dispersed in a mixed solution of ethylene glycol and dimethylacetamide, and reacted at 180° C. After the reaction is completed, the tin nanosheets are cooled and centrifuged to obtain the tin nanosheets.
[0045] The main reason why the steps of synthesizing the mixed phase structure palladium tin nanocrystals of the present invention are divided into two steps is that after synthesizing tin nanosheets in the first step, palladium tin nanocrystals are obtained by a substitution reaction between palladium and tin in the second step. During the substitution reaction, the rate of the substitution reaction is the key to determining that the obtained palladium tin nanocrystals are mixed phase structures, and only with an appropriate substitution reaction rate can such a mixed phase structure be obtained. Therefore, in the synthesis process of palladium tin nanocrystals, the substitution reaction rate is regulated to obtain a mixed phase structure by dividing into two steps.
[0046] In one embodiment, obtaining the tin nanosheet solution further comprises: obtaining tin nanosheets after centrifugal washing of the tin nanosheet solution; dispersing the tin nanosheets in an ethanol solution for storage, thereby ensuring the morphology of the tin nanosheets, resulting in a final product having a mixed phase structure.
[0047] Embodiment 1:
[0048] 1) Disperse 1 mL of tin acetylacetonate, tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone (PVP), and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide; then place it in an oil bath and react at 180° C. for 1 h. After the reaction is completed, centrifuge and wash it, then disperse it in 2 mL of ethanol solution for storage.
[0049] 2) Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheets in 2 mL of DMSO, ultrasonicate for 10 min, and stir until completely dissolved to obtain a uniform mixed solution; place the obtained uniform mixed solution in an oil bath at 180° C. for reaction for 15 minutes; after the reaction, centrifuge and wash to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.38 .
[0050] This embodiment is the best embodiment of the present invention, and the detailed characterization of the obtained product as a catalyst is as follows:
[0051] like Figure 1 and Figure 2 As shown, they are the bright field image and dark field image transmission electron microscopy characterization of the mixed phase structure palladium tin nanocatalyst. In both figures, it can be clearly seen that the overall morphology of the palladium tin nanocatalyst is a spherical nanoparticle structure.
[0052] like Figure 3 The figure shows a high-resolution transmission electron micrograph of one region of the palladium-tin nanocatalyst, which demonstrates the good crystallinity of the palladium-tin nanoparticles. The interplanar spacing is 0.23 nanometers, belonging to the (111) crystal plane of the face-centered cubic structure palladium-tin nanoparticles. Figure 4 This is a high-resolution transmission electron microscopy image of another area, the interplanar spacing is 0.13 nanometers, belonging to the (022) crystal plane of the ordered metal intermetallic structure palladium tin nanoparticles. Figure 3 and Figure 4 It can be seen that the synthesized palladium-tin nanocatalyst has a mixed phase structure of face-centered cubic and ordered intermetallic structure.
[0053] like Figure 5 As shown, it is a size statistics diagram of the product of this example, and the size of a single nanoparticle is about 7.39 nanometers.
[0054] like Figure 6 The figure shows the X-ray diffraction pattern of the product, which further shows that the palladium-tin nanocatalyst has a mixed phase structure of face-centered cubic and ordered intermetallic structure. The four typical diffraction peaks at 40.03°, 46.57°, 68.04° and 82.01° correspond to the (111), (200), (220) and (311) crystal planes of face-centered cubic palladium-tin, respectively. The diffraction peak at 31° corresponds to the (011) crystal plane of palladium-tin nanoparticles with ordered intermetallic structure.
[0055] Compared with the prior art, the palladium-tin nanocatalyst of the present invention does not require the presence of a carbon carrier during the preparation and synthesis process, and has a mixed phase structure (a mixture of an intermetallic structure and a face-centered cubic structure). The mixed phase structure particles construct a two-phase interface inside the nanoparticles, providing more active sites for the catalyst reaction. Obviously, it is impossible to infer such a mixed phase structure based on the currently available technology.
[0056] Embodiment 2:
[0057] 1) Disperse 1 mL of the reagent tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone (PVP) and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide; then place it in an oil bath and react at 180° C. for 1 h. After the reaction is completed, centrifuge and wash it, then disperse it in 2 mL of ethanol solution for storage.
[0058] 2) Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheets in 2 mL of DMSO, ultrasonicate for 10 min, and stir until completely dissolved to obtain a uniform mixed solution; place the obtained uniform mixed solution in an oil bath at 140° C. for reaction for 15 minutes; after the reaction, centrifuge and wash to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.17 .
[0059] like Figure 7 As shown, it is a bright field transmission electron microscope image corresponding to the product of this embodiment. From this image, it can be seen that the overall morphology of the product presents a spherical structure.
[0060] Embodiment 3:
[0061] 1) Disperse 1 mL of tin acetylacetonate, tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone (PVP), and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide; then place it in an oil bath and react at 180° C. for 1 h. After the reaction is completed, centrifuge and wash it, then disperse it in 2 mL of ethanol solution for storage.
[0062] 2) Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheets in 2 mL of DMSO, ultrasonicate for 10 min, and stir until completely dissolved to obtain a uniform mixed solution; place the obtained uniform mixed solution in an oil bath at 150° C. for reaction for 15 minutes; after the reaction, centrifuge and wash to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.18 .
[0063] like Figure 8 As shown, it is a bright field transmission electron microscope image corresponding to the product of this embodiment. From this image, it can be seen that the overall morphology of the product presents a spherical structure.
[0064] Embodiment 4:
[0065] 1) Disperse 1 mL of tin acetylacetonate, tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone (PVP), and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide; then place it in an oil bath and react at 180° C. for 1 h. After the reaction is completed, centrifuge and wash it, then disperse it in 2 mL of ethanol solution for storage.
[0066] 2) Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheets in 2 mL of DMSO, ultrasonicate for 10 min, and stir until completely dissolved to obtain a uniform mixed solution; place the obtained uniform mixed solution in an oil bath at 160° C. for reaction for 15 minutes; after the reaction, centrifuge and wash to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.21 .
[0067] like Fig. 9 As shown, it is a bright field transmission electron microscope image corresponding to the product of this embodiment. From this image, it can be seen that the overall morphology of the product presents a spherical structure.
[0068] Embodiment 5:
[0069] 1) Disperse 1 mL of tin acetylacetonate, tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone (PVP), and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide; then place it in an oil bath and react at 180° C. for 1 h. After the reaction is completed, centrifuge and wash it, then disperse it in 2 mL of ethanol solution for storage.
[0070] 2) Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheets in 2 mL of DMSO, ultrasonicate for 10 min, and stir until completely dissolved to obtain a uniform mixed solution; place the obtained uniform mixed solution in an oil bath at 170° C. for reaction for 15 minutes; after the reaction, centrifuge and wash to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.23 .
[0071] like Fig.10 As shown, it is a bright field transmission electron microscope image corresponding to the product of this embodiment. From this image, it can be seen that the overall morphology of the product presents a spherical structure.
[0072] Embodiment 6:
[0073] 1) Disperse 1 mL of tin acetylacetonate, tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone (PVP), and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide; then place it in an oil bath and react at 180° C. for 1 h. After the reaction is completed, centrifuge and wash it, then disperse it in 2 mL of ethanol solution for storage.
[0074] 2) Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheets in 2 mL of DMSO, ultrasonicate for 10 min, and stir until completely dissolved to obtain a uniform mixed solution; place the obtained uniform mixed solution in an oil bath at 190° C. for reaction for 15 minutes; after the reaction, centrifuge and wash to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.48 .
[0075] like Fig.11 As shown, it is a bright field transmission electron microscope image corresponding to the product of this embodiment. From this image, it can be seen that the overall morphology of the product presents a spherical structure.
[0076] The invention also discloses a mixed phase structure palladium tin nano catalyst, which is prepared by the above method. The mixed phase structure palladium tin nano catalyst is a mixed phase structure of face-centered cubic and ordered intermetallic structure.
[0077] The invention also discloses the application of the mixed-phase structured palladium-tin nanocatalyst. The mixed-phase structured palladium-tin nanocatalyst is used in the electrocatalytic reaction of ethanol oxidation.
[0078] Specifically, when the catalyst is used in an ethanol oxidation electrocatalytic reaction:
[0079] 6 mg of carbon-supported palladium tin catalyst was dispersed in 1 mL of a mixed solution of water, isopropanol and Nafion (volume ratio of water: isopropanol: Nafion solution = 1:1:0.01); 6 μg of the above ultrasonically homogenized sample was dropped on an area of 0.196 cm 2 The surface of the glassy carbon electrode was dried and then electrochemical testing was performed.
[0080] The electrochemical test was carried out at room temperature, the reference electrode was a Hg / HgO electrode, and the auxiliary electrode was a platinum mesh electrode (1×1 cm 2 ). Using a three-electrode system, in 1M KOH medium, such as Fig.12 As shown, the cyclic voltammetry curve was tested in N2 atmosphere, with a scan rate of 50mV / s and a scan range of 0.05V to 1.2V. Fig.13 , 14 As shown, the scanning was carried out in a mixed solution of 1 M KOH and 1 M C2H5OH, with a scanning rate of 50 mV / s.
[0081] Transform the test data into Fig.15 and Fig.16 As shown, they are the activity per unit mass of palladium ( Fig.15 ) and the activity of palladium per unit area ( Fig.16), it can be clearly observed that compared with the commercial Pd / C nanocatalyst, the catalytic activity of the mixed phase structure palladium tin nanocatalyst prepared by the present invention is significantly enhanced for the ethanol oxidation reaction. 0.38 The nanocatalyst has the best mass activity (2446.09 mA mg Pd -1 ) and area activity (8.85 mA cm -2 ), a commercial Pd / C nanocatalyst (849.16 mA mg Pd -1 , 3.4 mA cm -2 ) are 2.88 and 3.57 times.
Claims
1. A method for preparing a mixed phase structure palladium tin nanocatalyst, characterized in that: include: Dispersing tin nanosheets and sodium chloropalladate in DMSO, and ultrasonicating to obtain a uniform mixed solution; wherein the molar ratio of the tin nanosheets and sodium chloropalladate in the uniform mixed solution is (1-4):1; The uniform mixed solution is stirred at 140-190° C. until the reaction is completed to obtain a mixed phase structure palladium tin nanocatalyst; the mixed phase structure palladium tin nanocatalyst is a mixed phase structure of face-centered cubic and ordered intermetallic structure.
2. The method for preparing a mixed phase structure palladium tin nanocatalyst according to claim 1, characterized in that: The preparation method of the tin nanosheet is as follows: Tin acetylacetonate, polyvinyl pyrrolidone and ammonium bromide were weighed and dispersed in a mixed solution of ethylene glycol and dimethylacetamide, and reacted at 180° C. After the reaction was completed, the solution was cooled and centrifuged to obtain tin nanosheets.
3. The method for preparing a mixed phase structure palladium tin nanocatalyst as claimed in claim 2, characterized in that: include: Disperse 10 mg of sodium chloropalladate and 0.2 mL of tin nanosheet solution in 2 mL of DMSO and stir by ultrasonic until completely dissolved to obtain a uniform mixed solution; The uniformly mixed solution is placed at 180° C. until the reaction is complete; The solution after the reaction was centrifuged and washed to obtain a mixed phase structure of palladium tin nanocatalyst PdSn 0.38 .
4. The method for preparing a mixed phase structure palladium tin nanocatalyst according to claim 3, characterized in that: The preparation method of the tin nanosheet is as follows: Disperse 1 mL of tin acetylacetonate, 0.1 g of polyvinyl pyrrolidone, and 0.015 g of ammonium bromide in a mixed solution of 8 mL of ethylene glycol and 2 mL of dimethylacetamide; The dispersed mixed solution is placed at 180° C. for reaction, and a tin nanosheet solution is obtained after the reaction is completed.
5. The method for preparing a mixed phase structure palladium tin nanocatalyst according to claim 4, characterized in that: Obtaining the tin nanosheet solution also includes: After centrifugation and washing of the tin nanosheet solution, tin nanosheets are obtained; The tin nanosheets are dispersed in an ethanol solution and stored.
6. A mixed phase structure palladium tin nanocatalyst, characterized in that: The mixed phase structure palladium tin nanocatalyst is prepared by the method described in any one of claims 1 to 5, and the mixed phase structure palladium tin nanocatalyst is a mixed phase structure of face-centered cubic and ordered intermetallic structure.
7. The use of the mixed phase structure palladium tin nanocatalyst as claimed in claim 6, characterized in that: The mixed phase structure palladium tin nanocatalyst is used in the ethanol oxidation electrocatalytic reaction.
